2017
DOI: 10.3390/en10040547
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Organic and Steam Rankine Cycle Power Systems for Waste Heat Recovery on Large Ships

Abstract: This paper presents a comparison of the conventional dual pressure steam Rankine cycle process and the organic Rankine cycle process for marine engine waste heat recovery. The comparison was based on a container vessel, and results are presented for a high-sulfur (3 wt %) and low-sulfur (0.5 wt %) fuel case. The processes were compared based on their off-design performance for diesel engine loads in the range between 25% and 100%. The fluids considered in the organic Rankine cycle process were MM(hexamethyldis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…Also, research has shown that ORC has clearly a better performance when compared to Steam Rankine Cycle (SRC) (using water as the working fluid). It enables internal heat recovery, higher turbine efficiencies, and net power outputs [26]. R245fa was 352 chosen as a working fluid because, when compared with refrigerants such as R11, R114 or R141b, it has zero Ozone Depletion Potential, lower global warming potential, low toxicity, and it is non-flammable [27].…”
Section: Thermodynamic Modelling and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, research has shown that ORC has clearly a better performance when compared to Steam Rankine Cycle (SRC) (using water as the working fluid). It enables internal heat recovery, higher turbine efficiencies, and net power outputs [26]. R245fa was 352 chosen as a working fluid because, when compared with refrigerants such as R11, R114 or R141b, it has zero Ozone Depletion Potential, lower global warming potential, low toxicity, and it is non-flammable [27].…”
Section: Thermodynamic Modelling and Simulationmentioning
confidence: 99%
“…To assess the sustainability of this investment Eq. 20- (26) were used ( Table 3). For the risk analysis, the Monte Carlo simulation of palisade @risk tool was used.…”
Section: Economic Analysismentioning
confidence: 99%
“…While, engine coolant is a relative low grade waste heat, whose temperature is below 100 • C, but still significant due to the comparative amount of waste heat [2]. Using a thermodynamic cycle to generate extra power is a high-efficiency way among the technologies of E-WHR, mainly including single-loop organic Rankine cycle (ORC) [3,4], dual-loop ORC [5,6], steam Rankine cycle [7,8], CO 2 -based transcritical Rankine cycle (CTRC). Moreover, thermodynamic cycle is a feasible scheme to make a combined recovery of exhaust gas and engine coolant.…”
Section: Introductionmentioning
confidence: 99%
“…However, given the high sensitivity between the fluid properties and the cycle process operating conditions and performance, this is a challenging tasks with existing heuristic approaches [38]. Recent literature point at the need for use of CAMD techniques for finding novel refrigerants [25].…”
Section: Figure 4: Vapor-compression Cyclementioning
confidence: 99%